Propriedades reológicas da goma diutana em solução aquosa e sua aplicação em fluidos de perfuração: efeitos da concentração, salinidade e temperatura - Santos, Valeria Silva dos (2023)
The objective of this work was to study, from the application of rheological, viscosity and viscoelastic tests, the behavior of diutan gum in aqueous solution, submitted to different conditions of polymeric concentration (0.75 g/L; 1 g/L; 1, 25 g/L; 1.5 g/L and 1.75 g/L), salinity (3 g/L; 30 g/L; 60 g/L and 90 g/L of NaCl) and temperature (4 °C ; 25°C; 40°C; 60°C and 80°C). As a complement, Fourier Transform Infrared Spectroscopy (FTIR) tests were carried out to verify the behavior of the chemical structure of diutan and its functional groups, with the environment being disturbed. The applied methodology consisted in the preparation of aqueous solutions from a base step, characterized by the addition of dry diuthan gum to distilled water (15000 RPM for 10 minutes). Some conditions and parameters were varied throughout the base step according to the specific objective of the test, in this case concentration, temperature and salinity. Then rheological tests were performed on the Anton Paar MCR 72 (viscosity) and Anton Paar Physica MCR 501 (viscoelasticity) rheometers. FTIR spectra were performed on an Agilent Cary 630 FTIR spectrometer with a ZnSe crystal at a resolution of 4 −1 and an accumulation of 128 scans. The rheological results showed that the concentration of 0.75 g/L presented a low dynamic modulus and part of the flow dominated by the viscous component. In saline medium, the viscoelasticity was dominated by the elastic component (G'>G") with a low dynamic modulus, indicating the formation of a weak gel. Regarding the temperature, the flow curves remained pseudoplastic and the apparent viscosity presented a plateau at high shear rates (100−1 – 1000−1), at the respective temperatures of 40°C, 60°C and 80°C. In general, diutane gum in aqueous solution showed a good ability to remain stable under adverse conditions, involving changes in salinity and temperature increase. Many authors attribute this fact to the perfect double helix conformation that this polysaccharide forms in solution. Spectroscopy obtained by FTIR, in samples contaminated with NaCl or subjected to temperature gain, showed that the chemical structure of diutan remained stable without suffering loss of functional groups. This stability is the result of three factors, its chemical structure and location of its side chains, ability to form a perfect double helix in an aqueous medium and ability to retain water inside the core of the helix conformation. All these aspects place diutana as a potential biopolymer for application in aqueous drilling fluids, mainly in complex fields such as the Brazilian pre-salt, where adverse conditions of salinity and temperature are more common.